Propagation of False Information on Covid-19 among Nigerians on Social Media - Eric Msughter Aondover; Uchendu Chinelo Ebele; Timothy Ekeledirichukwu Onyejelem; Omolara Oluwabusayo Akin-Odukoya (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
Social media has become an indispensable aspect of modern life since it enables the distant creation of material for the purposes of amusement and information exchange, facilitating quicker and easier information sharing in Nigeria and around the globe. Through social networks and online communities, social media, as computer-mediated technology, promotes the development and exchange of concepts, awareness, professional interests, information, and other forms of expression. In Nigeria, the Covid-19 outbreak ushered in a digital age of first-ever marketing. During that time, citizens used social media to raise awareness among the public and demand action from the government to stop the spread of the virus. Within this conceptual context, the postulation of Technological Determinism theory serves the study goal. The study used secondary data to generate information on the subject matter. These sources provided concrete context for the thematic area of analysis. To interrogate the literature, a content analysis of secondary data was conducted. This made it possible to assess the body of knowledge in order to determine its applicability, consistency, and replication. It was established that customers used to rely on more traditional media, including radio and television, which included comparatively fewer and more reputable news sources. Consumers today are exposed to online information sources (the Internet), which was created to spread information and shape public opinion on topics by dictating what information is made available. The study concludes that the way that real-time audience participation has led to crowd sourcing content, which reflects the effects of rapidly evolving digital technology, online behaviors, and newsgathering techniques that has transformed journalistic practice as a result of social media. Members of a network can now communicate globally as a result of web-based applications, which facilitate the spread of fake information.